Mechanical response of cross-tensioned concrete pavement: experimental study and finite element. Issue 1 (6th December 2023) - Chen, Zhenglei; Wang, Guanhu; Meng, Chaomei; Shao, Bin; Shen, Yong
ABSTRACT: The cross-tensioned concrete pavement (CTCP) has good bearing capacity, anti-crack ability and convenient construction characteristics due to the cross-tenioned prestressed strands placed inside the concrete. In order to study the mechanical response of pavement in construction process, an assembled monolithic structure for CTCP has been proposed and its mechanical response was analyzed through full-scale experiments and finite element model. The results of full-scale experiments show that the longitudinal and transverse compressive strain of concrete respectively exceeds 40μϵ and 20μϵ in the area of laying cross-tensioned prestressed strands with increase of the number of cross-tensioned strands. The end of CTCP is one of the weak areas, which may produce certainly transverse tensile stress. The results of finite element model show that the transverse tensile stress in ending region is mainly affected by the angle of cross-tensioned prestressed strands and its ratio. There is transverse tensile stress at the end of the pavement when the angle of cross-tensioned prestressed strands is small and its ratio is large, which can be offset by arranging transverse prestressed strands. Furthermore, an empirical formula to calculate transverse prestressed strands ratio at the end of pavement is given based on the results of finite element simulation.